Renal Artery Stenosis: Diagnostic and Management Problems - Samsu, Nur; Waafi, Affa Kiysa (Clinical and Research Journal in Internal Medicine, 2020)
Renal artery stenosis is one common clinical problem. It has wide spectrum of pathophysiology with 3 most common clinical syndromes, ischemic nephropathy, hypertension, and cardiac destabilization syndrome. Aim: To date there was not any specific diagnostic criteria for renal artery stenosis. Method: Clinicians only used some clinical syndromes to guide the diagnostic possibility of renal artery stenosis. RADUS as one sensitive and specific diagnostic method, still had some disadvantages. Results: it gives false negative results in 10-20% of patients due to confounding factors such as operator capability, obesity, or abdominal gas distribution. CTA and MRA was excellent, but possessed some risks for the patient. Therefore, CTA was mostly recommended in patient with the planning of revascularization. Management of renal artery stenosis was still debated between optimal medical management and revascularization because the complexities of mechanisms underlying the renal artery stenosis. Because of the complicated pathophysiology of renal artery stenosis, revascularization could not entirely improve renovascular hypertension and nephropathy. Revascularization offered best results in fibromuscular dysplasia, although procedure related complication was still high. Revascularization, even though it might have high success rate in atherosclerotic renal artery stenosis, but the incidence of re-stenosis was also fairly high. Conclusion: Overall, revascularization was recommended in FMD, but should only be preserved for atherosclerotic renal artery stenosis after the failure of optimal medical management.